Agent-Mediated Electronic Commerce. Designing Trading Strategies and Mechanisms for Electronic Markets AMEC 2013, Saint Paul, MN, USA, May 6, 2013, TADA 2013, Bellevue, WA, USA, July 15, 2013, and AMEC and TADA 2014, Paris, France, May 5, 2014, Revised Selected Papers - Ceppi, Sofia; David, Esther; Podobnik, Vedran; Robu, Valentin; Shehory, Onn; Stein, Sebastian; Vetsikas, Ioannis A. (Springer eBooks, 2014)
This volume contains 12 thoroughly refereed and revised papers detailing recent advances in research on designing trading agents and mechanisms for agent-mediated e-commerce. They were originally presented at three events: the Workshop on Agent-Mediated Electronic Commerce (AMEC 2013), co-located with AAMAS 2013 in Saint Paul, MN, USA, in May 2013; the Workshop on Trading Agent Design and Analysis (TADA 2013), co-located with AAAI 2013 in Bellevue, WA, USA, in July 2013; and the Joint Workshop on Trading Agent Design and Analysis (TADA 2014) and Agent-Mediated Electronic Commerce (AMEC 2014), co-located with AAMAS 2014 in Paris, France, in May 2014. Given the breadth of research topics in this field, the range of topics addressed in these papers is correspondingly broad. These include the study of theoretical issues related to the design of interaction protocols and marketplaces; the design and analysis of automated trading strategies used by individual agents; and the deployment of such strategies, in times as part of an entry to the trading agent competition.